Frequency-Dependent Changes in Interhemispheric Functional Connectivity Measured by Resting-State fMRI in Children With Idiopathic Generalized Epilepsy - Jiang, Lin; Ma, Xuejin; Li, Shiguang; Luo, Hongjian; Zhang, Guoming; Wang, Yanan; Zhang, Tijiang (Frontiers in Neurology, 2020)
Epilepsy is associated with abnormal spatiotemporal changes in resting-state brain connectivity, but how these changes are characterized in interhemispheric coupling remains unclear. This study aimed to characterize frequency-dependent alterations in voxel-wise mirrored homotopic connectivity (VMHC) measured by resting-state functional magnetic resonance imaging (rs-fMRI) in children with idiopathic generalized epilepsy (IGE). Rs-fMRI data were collected in 21 children with IGE and 22 demographically-matched children with typical development. We used three resting-state frequency bands (full, 0.01-0.08 Hz; slow-4, 0.027-0.073 Hz; and slow-5, 0.01-0.027 Hz) to compute VMHC and locate the significant foci. Voxel-wise p < 0.001 and cluster-level p < 0.05, cluster-level family-wise error correction was applied. In between-group comparisons, we identified the full and higher frequency (slow-4 band) showing similar reductions in VMHC in children with IGE, including Rolandic operculum, putamen, superior frontal, lateral parietal, middle cingulate, and precuneus. In the lower frequency (slow-5) we identified specific reductions in VMHC in orbitofrontal and middle temporal gyri in children with IGE. Further analyses on main effects and interaction between group and frequency band suggested significant frequency-dependent changes in VMHC, and no significant interaction was found. These results were generally similar with global brain signal regression. Additional association analysis showed that VMHC in the putamen within full and slow-4 bands was significantly positively correlated with chronological age in children with IGE, and the same analysis was nonsignificant in the controls; VMHC in the medial prefrontal region in the slow-4 band was significantly positively correlated with IQ performance sub-score. Our findings suggest that IGE children show frequency-dependent changes in interhemispheric integration, that spans regions and systems that involving cortical-subcortical, language, and visuomotor processing. Decreased functional coupling within the dorsal striatum may reflect atypical development in children with IGE.